Protection Of Land Rights Of The Pantai Bahagia Village Community Based On National Agrarian Law - Gaffar Ahmad; Ridha Wahyuni (Green Publisher Indonesia, 2024)
The purpose of this research is to determine the protection of land rights for the residentsof Pantai Bahagia village based on national agrarian law. The method used is the juridical-empirical method. The juridical-empirical method is a research approach that examines thecurrent regulations as seen from the realities in society, or research that observes theapplication of the law in its actual state. The results of this study indicate that the form ofprotection of land rights that can be provided to the 2014 households in Pantai BahagiaVillage, who occupy land in forest areas, can be realized through the release of forest areas.The release of these forest areas is carried out through a request to the Ministry ofEnvironment and Forestry (KLHK), considering evidence of land ownership and historicaldata possessed by the community. With the release of the forest area, the community canthen register the land as their property rights, thus providing legal certainty over their land.